(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2017)
Phraseological units of each language have their own unique features, but there are similar features on the basis of which it is possible to distinguish universal features of phraseological units of different languages. Despite the fact that phraseologists from different countries use national terminology, the study of particular aspects of the content plan of phraseological units reveals a certain universality. Taking into account all the differences in the interpretation of different national phraseological scientific schools the motivated connection between components of phraseological units can be reduced to only three following universal types. Fixed phraseological units are units with set components, unmotivated, indecomposable, all components of which are redefined. Variable phraseological units are units that consist of one regular component and at least one unfixed component having direct meaning. Unfixed (unstable) phraseological units are such phraseological units, which include words with free meaning. By the criterion of semantic stratifications (in relation to phraseological nomination to reality), the following main types of phraseological units: with the nominative meaning, proverbial and non-proverbial phrases, modal, interjection and functional. It is established that the number of unfixed phraseological units is almost equal in the English and Russian phraseology, somewhat less in Belarusian and French, this fact proves that more fixed structure is more typical for the Belarusian and French phraseological units. The overwhelming number of the phraseological units of the Belarusian, Russian, English and French languages are nominative, that also indicates that the primary, the main function of phraseological units is to name (with various degrees of expressive evaluation) the realities of the surrounding world.